Behavioral java code generation from imperative object constraint language expressions in plataformindependent UML models - TAVARES, Marcellus Antonius de Castro (2011)
Antonius de Castro Tavares, Marcellus; Pierre Louis Robin, Jacques. Behavioral java code generation from imperative object constraint language expressions in plataformindependent UML models. 2011. Dissertação (Mestrado). Programa de Pós-Graduação em Ciência da Computação, Universidade Federal de Pernambuco, Recife, 2011.